Italian Consumers’ Readiness to Adopt Eggs from Insect-Fed Hens - Nico Lippi (MDPI AG, 2021)
Demand for eggs from laying hens is increasing as the world population continues to grow. The use of insects as animal feed is a strategic opportunity to find a new innovative, economic and sustainable source of protein. The aim of this study was to evaluate the Italian consumer inclination for eggs produced with the use of insect-fed hens. The investigation on consumers’ readiness to adopt eggs from insect-fed hens was carried out through an online survey conducted on 510 participants. Survey results outlined four different clusters on the basis of the willingness to buy/eat eggs fed with insects: “ready” (40.1%), “environmentalist” (24.3%), “cautious” (21.7%), and “reluctant” (13.9%). “Ready”, “environmentalist”, and “cautious” were quite favorable to the use of insects as feed stuffs and share drivers for product choice: cheap, organic, and with an explicit indication of use of insects. On the other hand, for the “reluctant”, the diet based on insects was the main negative factor influencing product acceptance. This cluster also showed the highest level of neophobia. Italian consumers showed a considerable level of readiness to accept insects as feed material for egg production, which should be reinforced with further information on the origin and the environmental benefit of using insects.